REVIU DOKUMEN PERENCANAAN DAN PENGANGGARAN DALAM PENINGKATAN AKUNTABILITAS ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN TEGAL TAHUN 2023 - SAIDNO; SURYO EDIYONO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2023)
Reviewing planning and budgeting documents by the Government Internal Supervisory Apparatus (APIP) as an internal control is one of the strategic activities for managing the risk of fraud in the planning and budgeting process and to guarantee local government accountability. The scope and objectives of the review on regional planning and budgeting documents is about review and analysis of priority policies for development budget allocations, the suitability of inputs to produce output in implementation of performance-based budgeting, and feasibility analysis on budget efficiency according to spending and price directive standards. The results of reviewing planning and budgeting documents can be used as tools of mitigation and to reduce fraud in planning and budgeting of local government. The strategy of reviewing planning and budgeting documents is how to manage the risk of fraud in the planning and budgeting process and to guarantee local government accountability that system and mechanism has not been established to execute the results of the review as a condition for validating planning and budgeting documents. Therefore, corrections and mitigation of the review not being fully followed up, and risk management in order to reduce fraud in the planning and budgeting process were not optimal